Methods for the determination of composition, mineral phases, and process-relevant behavior of ashes and its modeling: A case study for an alkali-rich ash. (February 2022) - Reinmöller, Markus; Kong, Lingxue; Laabs, Marcel; Ge, Zefeng; Hommel, Caroline; Farid, Massoud Massoudi; Shi, Wenju; Schreiner, Marcus; Cao, Xi; Guhl, Stefan; Bai, Jin; Meyer, Bernd
Abstract: The mineral matter contained in feedstocks has a generally limiting impact on the process design of high-temperature conversion processes. In the present study, the composition, mineral phases, and process-relevant properties of ashes are investigated by different experimental and modeling methods, which were reviewed in the literature regarding the frequently applied methods. Various analyses are exemplarily performed for the ashes of a high-sodium coal from China, generated at temperatures of 150–950 °C. X-ray fluorescence (XRF) analysis, microwave-assisted inductively-coupled plasma optical emission spectrometry (MW-ICP-OES), and the same technique with electrothermal vaporization (ETV-ICP-OES) are applied to analyze the chemical composition of the bulk material. The chemical composition of the near-surface region is studied by scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDX). Mineral phases are analyzed by X-ray diffraction (XRD) and thermochemical calculations. The process-relevant ash fusion behavior is studied by a common ash fusion test (AFT) and thermomechanical analysis (TMA) and supported by thermochemical calculations. The different ashing temperatures have a recognizable impact on the composition, formation and transformation of mineral phases, and resulting ash fusion behavior, while each property is monitored by at least two different methods. For this purpose, a detailed analysis of the results achieved by the individual methods is performed. Finally, the results obtained by different methods for the same ash property are compared for monitoring the validity of the results and, for example, extracting additional information about the gas phase transfer of selected ash components. Graphical abstract: Image 1 Highlights: A case study performed for a high-sodium fuel at ashing temperatures of 150–950 °C. Ash composition, mineral phases, and fusion behavior studied by multiple methods. Thermochemical calculations predict mineral phases and ash fusion behavior. Methodical cross-comparison allows verification and insights into ash transformations. Mechanisms of gas phase transfer and differences in slag formation concluded.